PENGARUH BIMBINGAN KLASIKAL TERHADAP NILAI KARAKTER PEDULI SISWA DI SMP NEGERI 2 KELAYANG (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Classical guidance is a guidance service in assisting all students in developing effective behavior and life skills which refers to the developmental tasks of students presented using classical guidance and group dynamics. The research entitled the influence of classical guidance on the value of students' caring character aims to determine the character values of students before and after classical guidance, to find out the differences and effects of classical guidance. This type of research is experimental researchers. The research subjects of class IX students were 20 students. The instrument used is a Likert scale. This research uses Wilcoxone test and Speaman Rank test. For the analysis using SPSS version 25. The results showed a significant influence on the influence of classical guidance on the value of the caring character of students.Key Words: Classical Guidance, Caring Character Values